The economic effects of trade liberalization on Philippine agriculture - Clarete, Ramon L. (1989)
This paper evaluates the economic effects of the trade liberalization program on the Philippine agricultural sector, using a 25-sector computable general equilibrium model of the Philippine economy. The paper discusses the extent of the tariff reforms and the import liberalization program in agriculture, indicating the bias of these reforms against the agricultural sector. Their economic effects are computed using the CGE model. In addition to these reforms, the study also assesses the economic effects of alternative tariff policy reforms including uniform tariff rates, higher agricultural tariffs, and lower industrial tariffs.
Includes bibliographical references.
Keywords: Free trade; Computable general equilibrium models; Tariff -- Law and legislation